Childhood obesity and cardiovascular disease - Bridger, Tracey (Pulsus Group Inc, 2009)
Childhood obesity has reached epidemic proportions. Many of these children have risk factors for later disease, including cardiovascular disease. For optimal cardiovascular health, health care professionals must be able to identify children and youth at risk and provide appropriate support as needed. The present article reviews the current medical literature on obesity and cardiovascular disease risk factors in the paediatric population, the long-term cardiovascular consequences of childhood obesity and the importance of early life. Recommendations promoting optimal cardiovascular health in all children and youth are discussed.